Phosphomannomutase 2 hyperinsulinemia: Recent advances of genetic pathogenesis, diagnosis, and management - Chen, Congli; Sang, Yanmei (Frontiers in Endocrinology, 2023)
Congenital hyperinsulinemia (CHI), is a clinically heterogeneous disorder that presents as a major cause of persistent and recurrent hypoglycemia during infancy and childhood. There are 16 subtypes of CHI-related genes. Phosphomannomutase 2 hyperinsulinemia (PMM2-HI) is an extremely rare subtype which is first reported in 2017, with only 18 families reported so far. This review provides a structured description of the genetic pathogenesis, and current diagnostic and therapeutic advances of PMM2-HI to increase clinicians' awareness of PMM2-HI.